Development Of The “Langkah Ceria” Interactive Carpet Media To Improve Gross Motor Skills Of Early Childhood - Rini Nurbaning Janah; Hamid Patilima; Irma Yuliantina (Kirana Publisher (KNPub), 2026)
This study aims to develop the interactive carpet media “Langkah Ceria” to improve gross motor skills of early childhood. The research was motivated by the low level of gross motor development among children aged 5–6 years at TK Negeri Manonjaya, Tasikmalaya Regency, where many children had not achieved the expected developmental standards. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The research involved 75 children from five classes of Group B. Data were collected using a modified Gross Motor Function Measure (GMFM) instrument consisting of 15 indicators covering five domains: static balance, locomotor walking, locomotor jumping, manipulative coordination, and dynamic balance. The effectiveness of the developed media was tested using a one-group pretest–posttest design. The results show that the interactive carpet media is feasible and effective for learning activities. Expert validation from two material experts and one media expert yielded an average feasibility score of 91.3%, categorized as very feasible. The implementation results indicate an increase in the average gross motor score from 18.87 (41.9%) in the pretest to 29.29 (65.1%) in the posttest, with an average N-Gain score of 0.40 in the moderate category. These findings indicate that the “Langkah Ceria” interactive carpet can serve as an innovative and practical learning medium to support the development of gross motor skills in early childhood.